Dance-plyaska in Russia of the Silver Age - Sirotkina, Irina (Edinburgh: Edinburgh University Press, 2010)
RESUMEN: The present paper focuses on the semantic and cultural meaning of plyaska as a distinct and influential phenomenon of the Silver Age. In particular, the cult of dance-pyaska was responsible for both the welcome accorded to Isadora Duncan in Russia and the proliferation of groups, studios and theatres of free dance in Russia in the first decades of the twentieth century. The article will trace the rise and fall of the utopia of plyaska into the early Soviet years.